2006
DOI: 10.1038/sj.onc.1209389
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone receptors mutated in liver cancer function as distorted antimorphs

Abstract: Aberrant thyroid hormone receptors (TRs) are found in over 70% of the human hepatocellular carcinomas (HCCs) analysed. To better understand the role(s) of these TR mutants in this neoplasia, we analysed a panel of HCC mutant receptors for their molecular properties. Virtually all HCC-associated TR mutants tested retained the ability to repress target genes in the absence of T3, yet were impaired in T3-driven gene activation and functioned as dominant-negative inhibitors of wild-type TR activity. Intriguingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 82 publications
6
70
0
1
Order By: Relevance
“…The high levels of receptor expressed in MDA-TRh and SK-TRh could have contributed to the gain of ligandindependent effects, although ligand dependency was observed when transactivation of a TR-responsive plasmid was analyzed. Interestingly, a mutant receptor unable to bind T3 can cause thyroid tumors in mice (7), and different TR mutants defective in ligand binding were found in hepatocarcinomas (7,40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high levels of receptor expressed in MDA-TRh and SK-TRh could have contributed to the gain of ligandindependent effects, although ligand dependency was observed when transactivation of a TR-responsive plasmid was analyzed. Interestingly, a mutant receptor unable to bind T3 can cause thyroid tumors in mice (7), and different TR mutants defective in ligand binding were found in hepatocarcinomas (7,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Because the AP-1 complex regulates the expression of genes involved in oncogenic transformation and cellular proliferation (5), downregulation of AP-1 activity by the receptors could oppose unregulated cell growth. In addition, we have shown that TRs can block transformation by oncogenic ras, suggesting that they could play a relevant role as suppressors of ras-dependent tumors (6) and reduced expression of TRs and alterations in TR genes are common events in cancer, particularly in hepatocarcinoma and breast tumors (7)(8)(9)(10)(11). However, the role of TRs in tumor progression or metastatic growth is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced expression as well as somatic mutations in TRb1 are found at high frequency in human hepatocellular carcinoma (Chan and Privalsky, 2006), which frequently presents ras-activation (Ito et al, 1998). Furthermore, we have recently shown that this receptor acts as a suppressor of invasiveness and metastasis formation by hepatocarcinoma cells (MartıŽnez-Iglesias et al, 2009a, b), suggesting that it could represent a potential therapeutic target in cancer (Aranda et al, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…Nuclear receptors can also regulate the expression of genes that do not contain hormone response elements by the mechanism generally referred to as 'transcriptional cross-talk' with other transcription factors or signalling pathways (Gottlicher et al, 1998). Linking TRs and thyroid status to tumourigenesis, it has been reported that TH suppresses RAS-mediated transformation, alterations in TR expression in many human neoplasias and the presence of dominant-negative TR mutations in hepatocarcinomas (Gonzalez-Sancho et al, 2003;Garcia-Silva and Aranda, 2004;Chan and Privalsky, 2006). Moreover, TRb physically interacts with cell cycle regulators as cyclin D1 and p53 (Yap et al, 1996;Bhat et al, 1997;Barrera-Hernandez et al, 1998;Lin et al, 2002) and we have previously reported a specific role for apo-TRb in cell cycle control (Porlan et al, 2004).…”
mentioning
confidence: 99%